Nursing Care for Patients with Respiratory Failure to Meet Oxygenation Needs and Monitor Blood Sugar Levels - Albatta, Rana A. M.; Cahyati, Nur; Agriyanto, Destian haryu; A. M. Albatta, Rana (LPPM STIKES Guna Bangsa Yogyakarta, 2025)
Respiratory failure poses a critical medical challenge, often leading to emergency room visits and mortality. This study delves into of respiratory failure, focusing on the nursing management in meeting the oxygenation needs and blood sugar monitoring in patients with the condition of respiratory failure. Utilizing a descriptive approach with a case study methodology, the research was conducted in the ICU at Hospital in special region of Yogyakarta over a period of six days. Through observation, physical examination, and documentation analysis, the study aimed to understand the nursing intervention of meeting oxygenation requirements in respiratory failure patients, particularly through ventilator intervention and blood sugar monitoring. The study underscores the importance of individualized nursing care in addressing respiratory failure and optimizing patient care outcomes in the ICU setting.